Using Administrative Health Data to Define a Cohort of Youth Affected by Chronic Health Conditions: Preparing for Cross-Sectoral Data Linkage - Kyleigh Schraeder; Olesya Barrett; Alberto Nettel-Aguirre; Gina Dimitropoulos; Andrew Mackie; Susan Samuel (International Journal of Population Data Science, 2018)
Introduction In Alberta, 2,400 youth with chronic needs transition to adulthood every year, and many are not prepared for this change. Transferring youth from pediatric to adult-oriented care is poorly managed. To improve this process, we need to know how youth patients use health services during this period.